On the hyper-order of analytic solutions of linear differential equations near a finite singular point - Meryem Chetti; Karima Hamani (Mathematica Bohemica)
We study the hyper-order of analytic solutions of linear differential equations with analytic coefficients having the same order near a finite singular point. We improve previous results given by S. Cherief and S. Hamouda (2021). We also consider the nonhomogeneous linear differential equations.